11C-Choline PET/CT Identifies Osteoblastic and Osteolytic Lesions in Patients with Metastatic Prostate Cancer. (May 2015) - Ceci, Francesco; Castellucci, Paolo; Graziani, Tiziano; Schiavina, Riccardo; Chondrogiannis, Sotirios; Bonfiglioli, Rachele; Costa, Stefano; Virgolini, Irene J.; Rubello, Domenico; Fanti, Stefano; Colletti, Patrick M.
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to compare 11C-choline PET/CT, prostate-specific antigen (PSA), PSA kinetics, and 11C-choline uptake in recurrent metastatic prostate cancer patients with osteoblastic and osteolytic bone metastases. Patients and Methods We retrospectively analyzed 140 patients with the following criteria: (a) positive bone lesions identified with 11C-choline PET/CT and validated as true positive by histology (14.2%), correlative imaging (33.4%), or clinical follow-up (52.4%); (b) after radical prostatectomy (67.9%) or primary radiotherapy (22.1%); (c) proven biochemical relapse with rising PSA levels; (d) no chemotherapy, zoledronic acid, or palliative bone external beam radiation therapy previously administrated during biochemical relapse; and (f) asymptomatic for bone pain. Lesions were categorized as osteoblastic, osteolytic, or bone marrow lesions. Patients were divided into osteoblastic and osteolytic patient groups. Results 11C-Choline PET/CT detected oligometastatic bone disease (1–3 lesions) in 98 (70%) of the 140 patients and multiple bone lesions in 42 (30%) of the 140 patients. By per-lesion analysis of 304 lesions, there were 184 osteoblastic, 99 osteolytic, and 21 bone marrow lesions. By per-patient analysis, 97 (69.3%) of the 140 patients were in the osteoblastic group, whereas 43 (30.7%) of the 140 patients were in the osteolytic group. Statistically significant differences in SUVmax (P < 0.001), fast PSA doubling time (P = 0.01), and PSA velocity (P = 0.01) were observed between osteoblastic (lower values) and osteolytic (higher values) groups. By multivariate analysis, fast PSA doubling time was a significant predictor for osteolytic lesions. Conclusions We demonstrated differences in PSA kinetics and SUVmax between osteolytic and osteoblastic lesions. 11C-Choline PET/CT may identify patients that could benefit from early targeted therapies, depending on the type of bone lesions expressed.